Social Studies Repetitive? Exploring the Correlation between Student Perceptions, Motivation, and Learning Interest among PGSD Students - Celine Widyaningrum Kusumawardani; Dholina Inang Pambudi; Woro Sri Hastuti; Ikhlasul Ardi Nugroho; Supartinah (Universitas Pendidikan Ganesha, 2025)
This study is motivated by the tendency of Social Studies learning to focus on memorization and repetitive material without being accompanied by meaningful and contextual learning experiences. The aim of this study is to analyze the influence of students' perceptions of repetitive learning on their motivation and interest in learning Social Studies. A quantitative approach with a correlational method was employed, involving 42 elementary teacher education (PGSD) students selected through purposive sampling. The research instrument used was a questionnaire that had been tested for validity and reliability, and the data were analyzed using Pearson Correlation techniques. The results show that there is no positive relationship between perceptions of repetitive learning and learning motivation (r = 0.198; p = 0.209), nor with learning interest (r = 0.115; p = 0.467). However, a significant positive relationship was found between motivation and learning interest (r = 0.686; p = 0.000), indicating that motivation contributes to increased student interest in Social Studies learning. These findings suggest that repetitive learning alone is not sufficient to foster students' interest; therefore, learning strategies are needed that can enhance intrinsic motivation through more varied, contextual, and learner-centered approaches.